TECHNO ECONOMIC ANALYSIS OF BASIC PRICES OF SURFACE WATER FOR MINI-HYDRO POWER PLANTS - Muhamad Hakim Maulana; Rinaldy Dalimi (Green Publisher, 2022)
Studies this analyze application Policy price base water surface to generator electricity minihydro (PLTM) Where the mini-hydro power plant is also alternative for Upgrade ratio electrification in area remote areas so that they can help PLN as a company electricity owned by country which have not quite enough answer Upgrade ratio electrification areas isolated which still have limitations in use energy. The mini-hydro power plant utilizes water discharge as a raw materials to flow to the penstock and then to turbine and turbine the rotate generator for awaken energy electricity and water which has pass process flowed back to the river so that the water does not run out in use at the time of PLTM electricity production. But the government give rule to para investors private nor in country for pay price base water surface. This policy makes investors power generators mini-hydro power began to decrease. This study is expected to provide solutions for investors and entrepreneurs domestic companies wishing to invest in power plants power minihydro